The Logics of Party Formation Ecological Politics in Belgium and West Germany - Kitschelt, Herbert (Cornell University Press, 2019)
Drawing on interviews with more than 130 party activists, Herbert Kitschelt provides an incisive account of the development of three vanguard ecological parties in contemporary Western Europe-the Green party of West Germany, and the Belgian ecological parties Agalev and Ecolo